A STUDYING OF WEB CONTENT MINING TOOLS - Hany Salman, Rasha; Zaki, Mahmood; A. Shiltag, Nadia (Al-Qadisiyah Journal of Pure Science, 2020)
The web today has become an archive of information in any structure such content, sound, video, designs, and multimedia, with the progression of time overall web, the world wide web is now crowded with different data making extraction of virtual data burdensome process, web utilizes various information mining strategies to mine helpful information from page substance and web hyperlink. The fundamental employments of web content mining are to gather, sort out, classify, providing the best data accessible on the web for the client who needs to get it. The WCM tools are needful to examining some HTML reports, content and pictures at that point, the outcome is using by the web engine. This paper displays an overview of web mining categorization, web content technique and critical review and study of web content mining tools since (2011-2019) by building the table’s a comparison of these instruments dependent on some important criteria